Differential spatial distribution of white matter lesions in Parkinson's and Alzheimer's diseases and cognitive sequelae - Grey, Michael T; Mitterová, Kristína; Gajdoš, Martin; Uher, Richard; Klobušiaková, Patrícia; Rektorová, Irena; Rektor, Ivan (Journal of neural transmission (Vienna, Austria, 2022)
White Matter Lesions (WML) are a radiological finding common in aged subjects. We explored the impact of WML on underlying neurodegenerative processes. We focused on the impact of WML on two neurodegenerative diseases with different pathology. In this cross-sectional study of 137 subjects (78 female, 59 men, mean age 67.2; 43-87 years), we compared WML in healthy controls (HC; n = 55), patients with Alzheimer's disease and amnestic Mild Cognitive Impairment (aMCI), and Parkinson's disease patients with normal cognition and with MCI. Subjects with AD and aMCI were treated as one group (n = 40), subjects with PD and PDMCI were another group (n = 42). MRI T2_FLAIR sequences were analyzed. WML were divided into periventricular (pWML) or subcortical (sWML) depending on their distance from the ventricles. Subjects from the AD + aMCI group, had a significantly greater volume of WML than both HC and the PD + PDMCI group. The volume of WML was greater in the PD + PDMCI than in HC but the difference was not significant. In AD + aMCI subjects, sWML and not pWML were related to a decrease in global cognitive functioning despite greater volume of pWML. In PD + PDMCI, pWML correlate with decline in executive functions and working memory. In HC, pWML correlated with the multidomain decrease corresponding with the aging. This points to a difference between normal aging and pathological aging due to AD and PD brain pathology. The WML location together with underlying disease related neurodegeneration may play a role in determining the effect of WML on cognition. Our results suggest that the impact of WML is not uniform in all patients; rather, their volume, location and cognitive effect may be disease-specific.
Keywords: senioři; Cognitive Dysfunction; Cross-Sectional Studies; Disease Progression; Neuropsychological Tests; Cognition; PD; Alzheimer’s disease; progrese nemoci; bílá hmota; mužské pohlaví; Parkinson’s disease; Alzheimer Disease; průřezové studie; AD; Cognitive decline; White matter lesions; magnetická rezonanční tomografie; kognice; Magnetic Resonance Imaging; Periventricular; Parkinsonova nemoc; WML; ženské pohlaví; Nervous System Diseases; neuropsychologické testy; Cognitive domain; Humans; kognitivní dysfunkce; Parkinson Disease; White Matter; Subcortical; Alzheimerova nemoc; nemoci nervového systému; Female; Aged; MCI; lidé; Male